PENGEMBANGAN KAWASAN WISATA SUNGAI MEMPAWAH DENGAN KONSEP CBT SEBAGAI DAYA TARIK WISATA KOTA MEMPAWAH - Dicka Nertaya Borneo Pratama; Sulistyarini Sulistyarini; Agus Sugiarto (Universitas Tanjungpura, 2022)
The purpose study to determine direction the development Mempawah River tourism area with concept Community Based Tourism. This research provides benefits form opening up new job opportunities Sungai Mempawah tourist area in the City of Mempawah. Research method used descriptive with a qualitative type. This research was carried out in some Mempawah rivers in the City of Mempawah. Data collection methods this study were interviews, observations, and documentation. Data analysis technique used SWOT analysis with CBT.Results this study 1) Based general description, it shows that potential Mempawah river is very high to be developed into a river tourism area. 2) Based on the SWOT analysis, results are (a) mean strength the SWOT analysis 3.26, indicating a very high category. (b) mean weakness the SWOT analysis 1.86 high category (c) the mean opportunity SWOT analysis 3.26 very high category (d) mean threat SWOT analysis 2.14 high category. 3) Strategies developing mempawah river tourism area Mempawah City include (a) Involving community members decision making (b) certainty receiving benefits from tourism activities (c) preserving the preservation Mempawah river tourist area (d) maintaining unique local culture (e) direction its development is based on the supporting factors and inhibiting factors.